Influence of combined resistance training and healthy diet on muscle mass in healthy elderly women: a randomized controlled trial - Strandberg, Emelie; Edholm, Peter; Ponsot, Elodie; Wåhlin-Larsson, Britta; Hellmén, Erik; Nilsson, Andreas; Engfeldt, Peter; Cederholm, Tommy; Risérus, Ulf; Kadi, Fawzi (Journal of applied physiology (1985), 2015)
The delivery of efficient nonpharmacological treatment to prevent the loss of muscle mass in older adults is a major challenge, and information on the combined effects of training and diet is particularly important. Here we aimed to evaluate the effects of 24 wk of resistance training combined with a healthy dietary approach (n-6/n-3 ratio < 2) in a population of healthy and physically active older women (65-70 years). The three-armed randomized controlled trial included a resistance training + healthy diet group (RT-HD), a resistance training group (RT), and controls (CON). All subjects included in the study were physically active and had low levels of serum inflammatory markers. In accordance with the dietary goals, the n-6/n-3 ratio dietary intake significantly decreased only in RT-HD by 42%. An increase in 1 repetition maximum in leg extension occurred in RT (+20.4%) and RT-HD (+20.8%), but not in CON. Interestingly, leg lean mass significantly increased only in RT-HD (+1.8%). While there were no changes in serum C-reactive protein and IL-6 levels, a significant decrease in serum level of the pro-inflammatory precursor arachidonic acid (−5.3 ± 9.4%) together with an increase in serum n-3 docosahexaenoic acid (+8.3%) occurred only in RT-HD. Altogether, this study demonstrates that the effects of resistance training on muscle mass in healthy older adults can be optimized by the adoption of a healthy diet.